Temporal trends in inequalities of the burden of HIV/AIDS across 186 countries and territories - Penghong Deng; Mingsheng Chen; Lei Si (BMC, 2023)
Abstract Background The Global Burden of Disease, Injuries, and Risk Factors Study (GBD) has reported that HIV/AIDS continues to take a disproportionate toll on global health. However, the trends in global inequality of HIV/AIDS burden have remained ambiguous over the past two decades. The objectives of our study were to assess the socioeconomic inequalities, and temporal trends of HIV/AIDS across 186 countries and territories from 2000 to 2019. Methods We extracted data from the GBD 2019, and conducted a cross-national time-series analysis. Age-standardized disability-adjusted life-year (DALY) rates were used to measure the global burden of HIV/AIDS. Gross national income (GNI) per capita was used to approximate the national socioeconomic status. Linear regression analysis was conducted to investigate the relationship between age-standardized DALY rates due to HIV/AIDS and GNI per capita. The concentration curve and concentration index (CI) were generated to evaluate the cross-national socioeconomic inequality of HIV/AIDS burden. A joinpoint regression analysis was used to quantify the changes in trends in socioeconomic inequality of HIV/AIDS burden from 2000 to 2019. Results A decrease in age-standardized DALY rates for HIV/AIDS occurred in 132 (71%) of 186 countries/territories from 2000 to 2019, of which 52 (39%) countries/territories achieved a decrease in DALYs of more than 50%, and 27 (52%) of the 52 were from sub-Saharan Africa. The concentration curves of the age-standardized DALY rates of HIV/AIDS were above the equality line from 2000 to 2019. The CI rose from − 0.4625 (95% confidence interval − 0.6220 to -0.2629) in 2000 to -0.4122 (95% confidence interval − 0.6008 to -0.2235) in 2019. A four-phase trend of changes in the CIs of age-standardized DALY rates for HIV/AIDS was observed across 2000 to 2019, with an average increase of 0.6% (95% confidence interval 0.4 to 0.8, P < 0.001). Conclusions Globally, the burden of HIV/AIDS has decreased over the past two decades, accompanied by a trend of narrowing cross-country inequalities of HIV/AIDS burden. Moreover, the burden of HIV/AIDS continues to fall primarily in low-income countries.